Kedudukan Akta Ikrar Wakaf Perspektif Hukum Islam dan Hukum Positif di Indonesia: The Position of Waqf Pledge Deeds From The Perspective of Islamic Law and Positive Law in Indonesia - Muchtar, Andi Dahmayanti; Dunia, Jujuri Perdamaian; Al Azizah, Nabilah; Risdayani; Musfirah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study examines the status of waqf deeds from the perspective of Islamic law and Indonesian positive law, in response to the increasing number of cases of reacquisition of waqf land due to the absence of such deeds. The study aims to analyse and compare the status of waqf deeds from the perspective of Islamic law and positive law in Indonesia. This study is a literature review with a normative and comparative approach using qualitative descriptive analysis. The results of the study show that the status of waqf deeds in Islamic law is valid with the existence of ṣigat ṣarīḥ, both verbal and written, although deeds remain important as a means of ḥifẓ al-māl. Conversely, in Indonesian positive law, the deed of waqf declaration occupies a fundamental position as both a pillar and a requirement for the validity of waqf, as well as serving as authentic evidence that guarantees legal certainty. This comparison emphasises that Islamic law places greater emphasis on the substance of the waqf declaration, while Indonesian positive law emphasises the formal aspects through the deed. Thus, this study provides an understanding that the deed of wakaf declaration plays an important role in creating legal order and certainty in wakaf practices in Indonesia. This study contributes to the development of Islamic law and positive law in Indonesia by explaining the importance of the deed of wakaf declaration in preserving wakaf assets and promoting public welfare, providing insights for policymakers, legal practitioners, and the general public.